Fragilidade e mortalidade de idosos em contexto de alta vulnerabilidade social: um estudo prospectivo - Menezes, Ana Laura Costa (2021)
Frailty is a multidimensional syndrome and a predictor of adverse outcomes in the elderly. The aim of this study was to identify changes in the levels of frailty and its relationship with mortality in the elderly in a context of high social vulnerability. This is a prospective cohort study. Two assessment surveys were carried out: one at the baseline (2015) and another after 36 months (2018) in the municipality of São Carlos - SP. For data collection, we used the Phenotype of Fragility, instruments for sociodemographic characterization, health conditions and mortality. The data were analyzed using the software R version 3.5.3 in R-Studio, in which descriptive analyzes were performed, where the quantitative variables were presented in the form of median and the qualitative variables in the form of absolute frequency. Kruskal-Wallis test was also performed; Equality of proportions test; Multinomial logistic regression; Kaplan-Meier survival analysis and Cox Regression. The project to which this study is linked was authorized by the Ethics Committee of the Federal University of São Carlos and the use of the database was authorized. In the first assessment, in 2015, carried out with 346 elderly people, there was a predominance of female elderly (56.4%) and aged between 60-69 years (53.2%). In the second assessment, in 2018, 223 elderly people were reevaluated, who were mostly female (57.4%) and aged between 70 and 79 years old (44.8%). Among those who died, there was a predominance of elderly men (64.5%) and aged between 70 and 79 years (38.7%). Among the fragile assessed in 2015, 36.8% remained in this condition, while 52.5% returned to pre-fragility and 11.8% became non-fragile. In relation to the pre-fragile, 25.4% became non-fragile, 57.9% remained as pre-fragile and 16.7% became fragile. Among those without fragility, 37.9% remained non-fragile, 58.6% became pre-fragile and 3.4% became fragile. In the first assessment, the male gender and the presence of depressive symptoms were configured as factors associated with pre-frailty and frailty. The age group from 70 to 79 years old, on the other hand, was associated with pre-frailty, while lower education and self-rated health were considered to be conditions associated with frailty. While higher education and better health-related quality of life were predictors of pre-frailty and frailty, respectively. Of the elderly who died, 15.6% were frail, 6.2% pre-frail and 3.4% non-frail. In the survival analysis, he identified a higher proportion of non-frail elderly compared to the frail (p = 0.027), as well as for female (p = 0.038), younger (p = 0.021), physically active (p <0.001), with good and excellent self-perception of health status (p <0.001), without urinary (p = 0.013) and fecal incontinence (p = 0.048) and absence of depressive symptoms (p = 0.043). As for the Cox regression model, it was found that frailty (p = 0.040), male gender (p = 0.030), age over 80 years (p = 0.009) and fecal incontinence (p = 0.020) were predictors for death. In conclusion there were changes in the prevalence of frailty, since in the second assessment the prevalence of frail elderly people decreased. However, most participants remained in a pre-fragile condition. There was also a relationship between frailty and mortality, as this condition being a predictor of death in the elderly in a context of high social vulnerability.